Celtic migrations - Heron, Denis Caulfield (Statistical and Social Inquiry Society of Ireland, 1853)
It may be observed that the Celtic races have ever been remarkable for sudden migrations. We do not find them well known to the early historians. Herodotus places them in the extreme West of Europe, beyond the pillars of Hercules. In the fotirth century before the Christian Era, the Celts of Gaul crossed the Apennines and overran Central and Southern Italy. According to Livy, two hundred years before that period, one multitude of the Gauls crossed the Ehine, and settled in the Hercynian Forest; another crossed the Alps, settled m the valley of the Po, and founded Milan. In the Gaelic invasion of Italy, they defeated the Romans in the battle of the Allia (U.C. 365), and were in possession of Rome for six months, with the exception of the Capitol. But, unlike the northern invaders, during the decline of the Roman Empire, they established no states in Central or Southern Italy, and retired loaded with booty. The Celts of Ireland now appear determined to try their fortunes in some other place, and are emigrating from this country at a rate that surpasses anything previously known and recorded in the history of the migrations of the human family.
Read January 19th 1852
Keywords: Migration; Celtic people; 314.15